TEACHER STRATEGIES IN INSTITUTING RELIGIOUS AND MORAL VALUES IN CHILDREN IN GROUP B AT TUNAS BANGSA KINDERGARTEN, MENTOKAN, CENTRAL LOMBOK - St Ma'arifah (JOETAL: Journal of Education, Teaching and Learning, 2025)
This study aims to determine the teachers' strategies for instilling religious and moral values ​​in group B children at Tunas Bangsa Mentokan Kindergarten, as well as the supporting and inhibiting factors in instilling religious and moral values ​​in group B children at Tunas Bangsa Mentokan Kindergarten. This qualitative study, using a descriptive approach at Tunas Bangsa Mentokan Kindergarten, aims to objectively describe the conditions at the research location using a series of words or sentences. The subjects were the class teachers and the principal, and the objects were the group B students at Tunas Bangsa Mentokan Kindergarten. Data collection techniques used were structured and unstructured interviews, observation, and documentation. Data analysis techniques used were data reduction, data presentation, and conclusion drawing (verification). Data validity in this study was checked using source triangulation and technical triangulation. The research results show that teachers' strategies for instilling religious and moral values ​​in children at Tunas Bangsa Mentokan Kindergarten include teaching them to recite the Iqro, short surahs (chapters), practicing prayer and ablution (wudu), being polite, being honest, respecting others, and greeting others before entering the classroom. These religious and moral values ​​are more easily understood and remembered by children because they are practiced consistently every day and can stimulate their interest in learning. In addition to the strategies practiced by teachers at school, several supporting and inhibiting factors hinder the process of instilling religious and moral values ​​in children. Supporting factors include support and encouragement from the institution in providing examples and practices to instill religious and moral values ​​through appropriate methods and practices. Inhibiting factors include a lack of support or reciprocity from parents and the children's environment.